2003
DOI: 10.1097/01.asn.0000083900.92829.f5
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Kidney Disease, Mortality, and Treatment Strategies among Patients with Clinically Significant Coronary Artery Disease

Abstract: ABSTRACT. Cardiovascular disease is an important cause of mortality among patients with chronic kidney disease (CKD). This study describes associations between CKD, cardiac revascularization strategies, and mortality among patients with CKD and cardiovascular disease. All patients undergoing cardiac catheterization at Duke University Medical Center (1995 to 2000) with documented stenosis ≥75% of at least one coronary artery and available creatinine data were included. CKD was staged using creatinine clearance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
119
2
6

Year Published

2004
2004
2007
2007

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 212 publications
(138 citation statements)
references
References 42 publications
11
119
2
6
Order By: Relevance
“…14 To the best of our knowledge, only 1 other study of patients with nondialysis kidney disease has included a nonrevascularized group. 17 Similar to the present results, CABG was associated with a survival benefit across all levels of kidney function, whereas PCI failed to offer a significant benefit among patients with severe (creatinine clearance Ͻ30 mL/min) kidney disease. 17 The lack of an improvement in survival for PCI among nondialysis kidney disease patients is less likely to be explained by atherosclerotic risk factors and accelerated atherogenesis, because dialysis patients would also be so exposed, and yet a benefit of PCI over no revascularization was apparent in the dialysis group.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…14 To the best of our knowledge, only 1 other study of patients with nondialysis kidney disease has included a nonrevascularized group. 17 Similar to the present results, CABG was associated with a survival benefit across all levels of kidney function, whereas PCI failed to offer a significant benefit among patients with severe (creatinine clearance Ͻ30 mL/min) kidney disease. 17 The lack of an improvement in survival for PCI among nondialysis kidney disease patients is less likely to be explained by atherosclerotic risk factors and accelerated atherogenesis, because dialysis patients would also be so exposed, and yet a benefit of PCI over no revascularization was apparent in the dialysis group.…”
Section: Discussionsupporting
confidence: 87%
“…17 Similar to the present results, CABG was associated with a survival benefit across all levels of kidney function, whereas PCI failed to offer a significant benefit among patients with severe (creatinine clearance Ͻ30 mL/min) kidney disease. 17 The lack of an improvement in survival for PCI among nondialysis kidney disease patients is less likely to be explained by atherosclerotic risk factors and accelerated atherogenesis, because dialysis patients would also be so exposed, and yet a benefit of PCI over no revascularization was apparent in the dialysis group. A possible mechanism for the poor survival after PCI among nondialysis kidney disease patients is their increased risk of acute renal failure, an event associated with a greater risk of adverse outcomes after coronary intervention.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…With regard to surgical treatments, there is general agreement that patients who have coronary heart disease (CHD) and CKD who warrant intervention do better with coronary artery bypass surgery than with percutaneous coronary angioplasty (9). In this regard, among 3608 patients who were enrolled in the Bypass Angioplasty Revascularization Investigation (10) that compared bypass with angioplasty, there were 76 with CKD.…”
Section: Ckd As a Modifier Of Secondary Outcomesmentioning
confidence: 99%
“…133,134 Based on estimated glomerular filtration rate (eGFR), previous studies have shown a powerful relationship between the severity of CKD and poor outcomes in ACS and STEMI patients. [135][136][137][138][139][140][141] Multiple possible mechanisms for the cardio-renal syndrome, the strong association between CKD and increased risk for death and cardiovascular disease, exist.…”
Section: Chronic Kidney Disease In Patients With Acsmentioning
confidence: 99%